Genetically proxied gut microbiota and cancer risk: a scoping review of Mendelian randomization studies - Yating Cui; Jianguo Xu; Qingyong Zheng; Junfei Wang; Caihua Xu; Mingyue Zhang; Jiang Li; Jinhui Tian (Archives of Public Health)
Abstract Background Cancer is a critical global health issue, and gut microbiota is considered a potential factor in the development of cancers. This review synthesizes evidence from Mendelian Randomization (MR) studies to explore the potential causal links between gut microbiota and cancer risk, thereby addressing the limitations inherent in observational studies. Methods We adopted a systematic literature review approach to search the PubMed, Embase, and Web of Science databases up to December 2023 for all MR studies examining the relationship between gut microbial diversity, strain-specific abundance, and cancer risk. Data extraction encompassed study design, study population, definition of microbial exposure, details of genetic instrument variables, sample size, effect estimates, and statistical significance. Given the diversity of genetic tools across different studies, the results of each study were presented in the form of a forest plot, and quality was assessed according to STROBE-MR criteria. Results We reviewed 12 MR studies involving the relationships between 91 gut microbiota species and 14 types of cancer. The studies found that 64 of these gut microbiota species have potential protective effects against cancers, while 52 show tendencies to promote cancer development. Additionally, the relationship between 17 gut microbiota species and cancer remains unclear. Notably, the same gut microbiota species may have distinctly different impacts on different types of cancer. Conclusion Diverse gut microbiota have varied impacts on different cancer types. This microbial influence on cancer is not static; it changes dynamically. These changes are linked to variations in inflammation, metabolite adjustments, and differences in gut barrier function.